Economic Road Map for the North-eastern Region - Lahiri, Ashok Kumar (Economic and Political Weekly, 2024)
The north-eastern region of India has low per capita income despite a favourable land-man ratio, rich resource endowment, and a high potential for growth and development. The challenges are connectivity, location in a troubled neighbourhood, and fractiona
Keywords: Agglomeration Economies; Economic Road Map; North-Eastern Region; Physical Infrastructure; Per Capita Income